Caracterización de los sistema de producción porcina en el Cantón Bolívar - Ganchozo Intriago, María Marcela (2022)
This research was developed with the objective of characterizing the swine production systems of Bolivar canton, in order to identify the current situation of the elements that comprise them. In order to fulfill the objective of the study, quantitative and qualitative evaluation methodologies were used through a survey and an observation sheet applied to 500 swine producers. In addition, a Vester matrix was applied to facilitate the identification of the problems with the greatest impact on the evaluation. The results show that the largest pig production is concentrated in the Quiroga parish (32%) with male producers (61%) with ages between 30-60 years old (51%), with a predominance of the backyard production subsystem (76%), sanitary problems, lack of technical assistance (63%), insufficient economic income from pig production (74%), poor management of solid and liquid waste from the facilities, facilities in poor condition (80%), inadequate management of hygiene and odors in the facilities. The most critical inconsistency detected in this study is sanitary problems, which correspond to the other factors established according to the prioritization of effects of the Vester matrix. The problems detected could promote inadequate levels of productivity in swine production, affecting the economic development of the producers, making it necessary to use training programs for producers on issues related to swine production by entities related to agricultural development.